Identification of promising drug candidates against NSP16 of SARS-CoV-2 through computational drug repurposing study. Issue 17 (22nd November 2021) - Vijayan, Viswanathan; Pant, Pradeep; Vikram, Naval; Kaur, Punit; Singh, T. P.; Sharma, Sujata; Sharma, Pradeep
Abstract: The recent outbreak of the SARS-CoV-2 virus leading to the disease COVID 19, a global pandemic has resulted in an unprecedented loss of life and economy worldwide. Hence, there is an urgent need to discover effective drugs to control this pandemic. NSP16 is a methyltransferase that methylates the ribose 2′-O position of the viral nucleotide. Taking advantage of the recently solved structure of NSP16 with its inhibitor, S-Adenosylmethionine, we have virtually screened FDA approved drugs, drug candidates and natural compounds. The compounds with the best docking scores were subjected to molecular dynamics simulations followed by binding free energy calculations using the MM-PBSA method. The known drugs which were identified as potential inhibitors of NSP16 from SARS-CoV-2 included DB02498, DB03909, DB03186, Galuteolin, ZINC000029416466, ZINC000026985532, and ZINC000085537017. DB02498 (Carba-nicotinamide-adenine-dinucleotide) is an approved drug which has been used since the late 1960s in intravenous form to significantly lessen withdrawal symptoms from a variety of drugs and alcohol addicts and it has the best MM-PBSA binding free energy of–12.83 ± 0.52 kcal/mol. The second best inhibitor, Galuteolin is a natural compound that inhibits tyrosinase enzyme with MM-PBSA binding free energy value of −11.21 ± 0.47 kcal/mol. Detailed ligand and protein interactions were analyzed and common residues across SARS-CoV, SARS-CoV-2, and MERS-CoV were identified. We propose Carba-nicotinamide-adenine-dinucleotide and Galuteolin as the potential inhibitors of NSP16. The results in this study can be used for the treatment of COVID-19 and can also form the basis of rational drug design against NSP16 of SARS-CoV-2.